2008
DOI: 10.1080/08860220802356218
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and Nitric Oxide in Patients on Chronic Hemodialysis

Abstract: Aim. To establish the role of endothelin-1 and nitric oxide in the pathogenesis of hypertension in patients on chronic aemodyalisis by correlating endothelin-1 and NO plasma concentrations to the level of arterial hypertension with respect to angiotensin-converting enzyme (ACE) inhibitor therapy. Methods. We determined plasma concentrations of endothelin-1 and NO in patients on chronic hemodialysis (CHD) before and after hemodialysis treatment. The study included 30 CHD patients and 20 healthy participants as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
(56 reference statements)
1
12
0
1
Order By: Relevance
“…Results of the study demonstrate that ProET-1 plasma concentrations are obviously increased in the subjects’ group with end-stage CKD and renal failure if compared with a group of apparently healthy subjects. Results are in accordance with the findings of other authors, who demonstrated increasing endothelin plasma concentrations with progression of renal failure [17,18]. Altered expression of microcirculation parameters with age is a commonly occurring phenomenon.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results of the study demonstrate that ProET-1 plasma concentrations are obviously increased in the subjects’ group with end-stage CKD and renal failure if compared with a group of apparently healthy subjects. Results are in accordance with the findings of other authors, who demonstrated increasing endothelin plasma concentrations with progression of renal failure [17,18]. Altered expression of microcirculation parameters with age is a commonly occurring phenomenon.…”
Section: Discussionsupporting
confidence: 92%
“…ProET-1 plasma concentrations in the subjects’ group with end-stage CKD demonstrate a statistically significant increase if compared with the subjects’ group with renal insufficiency. Endothelial injury is considered to initiate increased secretion of ET-1 and to effectuate vasoconstriction, increased intraglomerular pressure, and decreased glomerular filtration [17]. ET-1 concentrations are demonstrated to correlate with blood pressure, suggesting that ET-1 may contribute to hypertension [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, patients with renal impairment had elevated plasma NOx levels. These data are not unchallenged as some other studies report that NOx remains unchanged or even declines in renal failure . Moreover, net endogenous NOx generation may actually be lower in renal failure .…”
Section: Discussionmentioning
confidence: 61%
“…Mature ET-1 is excreted directly into the bloodstream and accumulates in the liver and lungs. 27,28 The plasma concentration of ET-1 in adults is normally between 0.4-8.1 pg/ml, 29,30 and between 4.2 fmol/ml and 8 pg/ml in the plasma of Wistar rats. 31,32 The level of ET-1 increase with age, from 1.02 pg/ ml in young women to 2.9 pg/ml in older women.…”
Section: Discussionmentioning
confidence: 99%